Contexts of Reflectivity of Contemporary Parents - Wiatr, Marta (INSTED: Interdisciplinary Studies in Education & Society, 2015)
The subject of consideration are contemporary parents, who exhibit a certain kind of attention towards upbringing, forming and orienteering? The development/growth of their descendants. I mean here these people, who in the world of multiple and competing choices, make decisions in a thoughtful, rational and metodological? way. They become to be known as reflective parents. The introduction of the reflectivity category into considerations on the contemporary parenthood is to open a news pace of conceptualising processes and phenomena connected with the fulfillment of the parental role, selfunderstanding in this role and in the relations with a child.